Orchid conservation development at Mudal River by using remote sensing - Baritoadi Buldan Rayaganda Rito; Muhammad Muhajir; Rahmadi Yotenka; Novendri Isra Asriny; R.A. Nurul F.A. Asnawi (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Daerah Istimewa Yogyakarta (DIY) is a district in Yogyakarta that contains various tourist attractions (ODTW) such as the Mudal River, attracting many local and international visitors each year. However, this region must be developed by identifying the best conservation position. Technology is required to explore the geographical aspects in establishing ecotourism in order to complete this process. This study sought to determine the most appropriate new development for the Mudal River, taking into account environmental variables, site area, orchid growing demands, ease of access, and commercialization. This is accomplished by employing a remote sensing technique based on the overlay technique. As a consequence of the investigation, three sites have been identified as the most plausible candidates. The analysis identified three areas that are most likely to be used as conservation sites: an orchid cultivation house, an orchid garden area that may be used as a photo location, and an orchid education garden.